2003
DOI: 10.1097/00002030-200301030-00006
|View full text |Cite
|
Sign up to set email alerts
|

Platelet- and megakaryocyte-derived microparticles transfer CXCR4 receptor to CXCR4-null cells and make them susceptible to infection by X4-HIV

Abstract: We postulate that both PMP and MegaMP may play a novel and important role in spreading HIV-1 infection by transferring the CXCR4 co-receptor to CD4+/CXCR4-null cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
264
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 306 publications
(273 citation statements)
references
References 34 publications
7
264
0
2
Order By: Relevance
“…Not only were significantly more metastatic foci found in the lungs of mice injected with PMV-covered LCC cells, but also there were significantly more LCC cells detected in the bone marrow cavities of these mice. As PMV have been shown to transfer G-protein-coupled 7-transmembrane-span receptors such as CXCR4 onto the surface of target cells, 11,12,14 it is reasonable to suggest that LCC cells pre-incubated with PMV acquired CXCR4 on their surface and responded to the SDF-1-rich environment of the bone marrow. Previously, we reported that all 5 human lung cancer cell lines studied here do not express the CXCR4 receptor 33 ; however, as shown in other models, cells can be rendered CXCR4-positive by PMV, and CXCR4 transferred by PMV may be functional as a coreceptor for HIV entry 14 or tether PMV ϩ cells to SDF-1 exposed on endothelium.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Not only were significantly more metastatic foci found in the lungs of mice injected with PMV-covered LCC cells, but also there were significantly more LCC cells detected in the bone marrow cavities of these mice. As PMV have been shown to transfer G-protein-coupled 7-transmembrane-span receptors such as CXCR4 onto the surface of target cells, 11,12,14 it is reasonable to suggest that LCC cells pre-incubated with PMV acquired CXCR4 on their surface and responded to the SDF-1-rich environment of the bone marrow. Previously, we reported that all 5 human lung cancer cell lines studied here do not express the CXCR4 receptor 33 ; however, as shown in other models, cells can be rendered CXCR4-positive by PMV, and CXCR4 transferred by PMV may be functional as a coreceptor for HIV entry 14 or tether PMV ϩ cells to SDF-1 exposed on endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…As PMV have been shown to transfer G-protein-coupled 7-transmembrane-span receptors such as CXCR4 onto the surface of target cells, 11,12,14 it is reasonable to suggest that LCC cells pre-incubated with PMV acquired CXCR4 on their surface and responded to the SDF-1-rich environment of the bone marrow. Previously, we reported that all 5 human lung cancer cell lines studied here do not express the CXCR4 receptor 33 ; however, as shown in other models, cells can be rendered CXCR4-positive by PMV, and CXCR4 transferred by PMV may be functional as a coreceptor for HIV entry 14 or tether PMV ϩ cells to SDF-1 exposed on endothelium. 12 Although it is apparent that PMV contain components that alone or in combination are responsible for the various effects observed, the particular components responsible remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations